مساهمة إدارة العلاقات العامة في تشجيع المبادرة الداخلية بالمؤسسة الأمنية دراسة ميدانية بأمن ولاية سوق اهراس - زعلاني عبير; شابي فردوس (My University, 2021)
Study summary: Through this study, we tried to find out the contribution of the Public Relations Department to encouraging the internal initiative of the security institution, by encouraging the various individual initiatives of the employees, by encouraging the various individual initiatives of the employees of the security institution, and motivating them, and this is manifested through material or moral rewards. Importance It is based on other interests as it is central and has an important aspect in empowering institutions of a formal nature such as the security institution, and thus achieving the goals that the institution aspires to. And the more well the communication was activated, the higher the institution rose and achieved what it aspired to. Accordingly, the main question of the study problem came as follows: How does the Public Relations Department contribute to encouraging the internal initiative in the security institution? This question includes the following sub-questions: 1- Are the methods of organizing public relations in the security establishment compatible with the criteria for building the internal initiative? 2- How do the activities of the Public Relations Department contribute to encouraging internal initiative? 3- What are the public relations management obstacles that prevent the promotion of internal initiative in the security establishment? In the theoretical framework, we dealt with everything related to the variables of the study, but in the methodological framework, we relied on the social survey method, which is one of the descriptive research methods, due to its suitability and the nature of the subject. Data collection on: observation, interview, form to carry out our study. Then the following results were obtained:  The public relations apparatus of the security establishment is an effective and pivotal apparatus that cannot be dispensed with.  Attention to transparency is an important part of the security institution to improve it.  Motivation in the security establishment is an urgent necessity to increase the creativity of the employees ---------------------------- ملخص الدراسة: سعينا من خلال هذه الدراسة إلى معرفة مدى مساهمة إدارة العلاقات العامة في تشجيع المبادرة الداخلية للمؤسسة الأمنية، من خلال تشجيع المبادرات الفردية المختلفة للعاملين في المؤسسة الأمنية، وتحفيزهم، ويتجلى ذلك من خلال المكافآت المادية أو المعنوية. تنبع أهميتها من اهتمامات أخرى، فهي محورية ولها دور مهم في تمكين المؤسسات ذات الطابع الرسمي كالمؤسسة الأمنية، وبالتالي تحقيق الأهداف التي تطمح إليها. وكلما كان التواصل فعالاً، ارتفع شأن المؤسسة وحقق ما تصبو إليه. وبناءً على ذلك، جاء السؤال الرئيسي لمشكلة الدراسة على النحو التالي: كيف تساهم إدارة العلاقات العامة في تشجيع المبادرة الداخلية في المؤسسة الأمنية؟ ويتفرع من هذا السؤال الأسئلة الفرعية التالية: 1- هل أساليب تنظيم العلاقات العامة في المؤسسة الأمنية متوافقة مع معايير بناء المبادرة الداخلية؟ ٢- كيف تُسهم أنشطة إدارة العلاقات العامة في تشجيع المبادرة الداخلية؟ ٣- ما هي معوقات إدارة العلاقات العامة التي تحول دون تعزيز المبادرة الداخلية في المؤسسة الأمنية؟ في الإطار النظري، تناولنا كل ما يتعلق بمتغيرات الدراسة، أما في الإطار المنهجي، فقد اعتمدنا على منهج المسح الاجتماعي، وهو من مناهج البحث الوصفي، لملاءمته وطبيعة الموضوع. وقد اعتمدنا على أدوات جمع البيانات: الملاحظة، والمقابلة، والاستمارة لإجراء دراستنا. وتوصلنا إلى النتائج التالية: يُعد جهاز العلاقات العامة في المؤسسة الأمنية جهازًا فعالًا ومحوريًا لا يمكن الاستغناء عنه. يُعد الاهتمام بالشفافية ركنًا أساسيًا في المؤسسة الأمنية للنهوض بها. يُعد التحفيز في المؤسسة الأمنية ضرورة ملحة لزيادة إبداع العاملين.
Keywords: دارة العلاقات العامة، المبادرة الداخلية، المؤسسة الأمنيةإ